2018
DOI: 10.1155/2018/3869106
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Deep Learning Model for Traffic Crash Prediction

Abstract: Machine-learning technology powers many aspects of modern society. Compared to the conventional machine learning techniques that were limited in processing natural data in the raw form, deep learning allows computational models to learn representations of data with multiple levels of abstraction. In this study, an improved deep learning model is proposed to explore the complex interactions among roadways, traffic, environmental elements, and traffic crashes. The proposed model includes two modules, an unsuperv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…Var calculates the correlation coefficient. (6) It is worth noting that the sequence of expansion and prediction might affect prediction accuracy. Based on previous-expansion, post-prediction, the expanding and forecasting sequence of the model is reversed to obtain the truck traffic flow result of previous-prediction, postexpansion.…”
Section: ) Truck Traffic Flow Prediction With Grumentioning
confidence: 99%
“…Var calculates the correlation coefficient. (6) It is worth noting that the sequence of expansion and prediction might affect prediction accuracy. Based on previous-expansion, post-prediction, the expanding and forecasting sequence of the model is reversed to obtain the truck traffic flow result of previous-prediction, postexpansion.…”
Section: ) Truck Traffic Flow Prediction With Grumentioning
confidence: 99%
“…This network is named as feedforward because there are no feedback connections in which output of the model are fed back into itself. [20][21][22][23] Neural network was developed from single neuron named perceptron. It categorizes a set of input into one of two classes.…”
Section: Single Layer Perceptronmentioning
confidence: 99%
“…Many studies for crashes at intersections have resulted in crash prediction models that could estimate the probability of crash occurrence. Dong et al [26] reported on a crash prediction model based on data from Knox County in Tennessee, U.S.A. From this study, it was observed that, for the selected 635 roadway segments, from 2010 to 2014, a total of 5365 traffic crashes reported included 135 (2.51%) major injury crashes (fatal and incapacitating injury), 1312 (24.46%) minor injury crashes, and 3917 (73.02%) PDO crashes. Table 2, shown above, can be further refined by applying an appropriate probability of occurrence to estimate the expected costs.…”
Section: Traffic Crash Costsmentioning
confidence: 99%
“…The CPI values were also used to adjust the expected cost values to the 2019 dollars (Table 3). Based on Dong et al [26], the severity probabilities were adopted on the previously defined KABCO scale as follows: Fatal Injury (K) (1.25%); Suspected Serious Injury (A) (1.26%); Suspected Minor Injury (B) (12.23%); Possible Injury (C) (12.23%); and No Apparent Injury (O) (73.02%). Using these crash severity proportions, the crash cost for category A can be estimated to be 0.0125 * $11,295,402, or $142,322.07, which we can round up to $150,000.…”
Section: Traffic Crash Costsmentioning
confidence: 99%